Defined pH-sensitive nanogels as gene delivery platform for siRNA mediated in vitro gene silencing. (16th October 2017) - Dimde, Mathias; Neumann, Falko; Reisbeck, Felix; Ehrmann, Svenja; Cuellar-Camacho, Jose Luis; Steinhilber, Dirk; Ma, Nan; Haag, Rainer
Abstract : An advanced cationic carrier system which combines high transfection efficiency with low cytotoxicity and a control over the release of the encapsulated genetic material by the reduction of the multivalent architecture upon pH triggered degradation was developed. Abstract : In the present study, a pH sensitive nanogel platform for gene delivery was developed. The cationic nanogels based on dendritic polyglycerol (dPG) and low molecular weight polyethylenimine units were able to encapsulate siRNA during the manufacturing process. The thiol-Michael nanoprecipitation method, which operates under mild conditions and did not require any catalyst or surfactant, was used to develop tailor-made nanogels in the sub-100 nm range. The incorporation of pH sensitive benzacetal-bonds inside the nanogel network enables the controlled intracellular release of the cargo. The functionality to transport therapeutic biomolecules was tested by an in vitro GFP-siRNA transfection assay. Encapsulated siRNA could silence GFP expressing HeLa cells (up to 71% silencing in GFP). Furthermore, significantly reduced toxicity of the nanogel platform compared to the non-degradable PEI was observed. These properties realize a new carrier platform in the field of gene therapy.